Induced defense in Eucalyptus trees increases with prolonged herbivory - GOMES DE OLIVEIRA, HAMILTON; MOLINA-RUGAMA, ADRIÁN JOSÉ; FADINI, MARCOS A. M.; REZENDE, DANIELA; SOTO-G., ALBERTO; OLIVEIRA, CLÉBER; PALLINI, ANGELO (Revista Colombiana de Entomología, 2010)
Mechanisms of defense in plants can be activated by external stimuli such as herbivory. It is well-known that such induced defense occurs after short periods of herbivory, but little is known about long-term induction. In this paper, we studied the effects of induced defenses of Eucalyptus trees on Thyrinteina arnobia (Lepidoptera: Geometridae) over four generations. The effects of induction of eucalypt plants seemed to increase gradually with prolonged periods of herbivory. To our knowledge it is the first demonstration that induced defense changes in a gradual way with long-term herbivory. This suggests that these trees, and possibly many other plants, gradually invest more in induced defense with prolonged herbivore attacks.